2020
DOI: 10.1108/ijoa-10-2019-1915
|View full text |Cite
|
Sign up to set email alerts
|

Workplace spirituality as a source for competitive advantage: an empirical study

Abstract: Purpose This paper aims to theorize and empirically examines the role of perceived spirituality in developing organization competitiveness. Design/methodology/approach The paper adopts a quantitative approach, where the structural equation modeling approached was applied to analyze a unique dataset collected from 550 health-care staff in two international hospitals in Iran. Findings The results show that although the workplace spirituality (WS) can indirectly enhance the development of competitive advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…As stated above, our research extends the work of Tombaugh et al (2011), Albuquerque et al (2014 and Saadatyar et al (2020) by examining spiritual expression in the context of health-care professionals during COVID-19. We empirically tested whether practicing spirituality at work had an impact on organizational commitment in a range of health-care personnel, including doctors, nurses, physicians, administrators, managers and cleaning staff, during a severe crisis.…”
Section: Theoretical Implicationsmentioning
confidence: 78%
See 3 more Smart Citations
“…As stated above, our research extends the work of Tombaugh et al (2011), Albuquerque et al (2014 and Saadatyar et al (2020) by examining spiritual expression in the context of health-care professionals during COVID-19. We empirically tested whether practicing spirituality at work had an impact on organizational commitment in a range of health-care personnel, including doctors, nurses, physicians, administrators, managers and cleaning staff, during a severe crisis.…”
Section: Theoretical Implicationsmentioning
confidence: 78%
“…nursing) in an organization, with less emphasis on including all kinds of roles and generating a holistic picture. For more detail, see the studies on primary health-care services in Portugal, Finland and among nursing staff in Mashhad city (Albuquerque et al , 2014; Lampinen et al , 2018; Saadatyar et al , 2020).…”
Section: Spiritual Expression At Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Udriyah et al (2019) found that innovation can improve compe titive advantages. Saadatyar et al (2020) confirmed that spirituality improves competitive advantages be cause spirituality increases organization commit ment, which is essential for competitive advantag es. Mathew et al (2018) affirmed that spirituality increases job satisfaction and, in the end, im proves the competitive advantages.…”
Section: Literature Reviewmentioning
confidence: 79%